Public Key Cryptography Based Approach for Securing SCADA Communications - Saxena, Anupam; Pal, Om; Saquib, Zia (Computer Networks and Information Technologies, 2011)
SCADA (supervisory Control and Data Acquisition) security has become a challenge in today’s scenario because of its connectivity with the world and remote access to the system. Major challenge in the SCADA systems is securing the data over the communication channel. PKI (public key infrastructure) is an established framework to make the communication secure. SCADA systems, normally have limited bandwidth and low computation power of RTUs (Remote Terminal Units); through the customization of general PKI we can reduce its openness, frequent transfer of certificates and possibility of DOS (Denial of Service) attacks at MTUs (Master Terminal Units) and RTUs. This paper intends for securing data over communication channel in SCADA systems and presents the novel solutions pivoted on key distribution and key management schemes.